Current Treatment Guidelines for Acromegaly - Melmed, S. (The journal of clinical endocrinology and metabolism, 1998)
Acromegaly, an indolent disorder of growth hormone (GH) hypersecretion is most typically caused by a somatotroph cell adenoma and may be treated by several modalities. Transsphenoidal surgical resection of micro-adenomas by experienced neurosurgeons results in biochemical normalization (postglucose GH <2 ng/mL, assay-dependent, age- and sex-matched IGF-I levels) in 70% of patients. However, over 65% of GH-secreting adenomas are invasive or macroadenomas, and over 50% of these patients have persistent postoperative GH hypersecretion. Irradiation of adenomas results in attenuation of GH secretion to more than 5 ng/mL in 50% of subjects after 12 yr. However, the percent of parents who normalize IGF-I levels is less certain. Most of these patients develop associated pituitary failure and rarely develop other local adverse effects. About 60% of patients receiving somatostatin analogs achieve normalized IGF-I levels. Efficacy of medical management with somatostatin analogs may be improved by increasing injection frequency, changing delivery modes to depot preparations, and in the future, development of novel SRIF receptor subtype-specific analogs. An integrated approach to acromegaly management based upon relative risks and benefits of the currently available therapeutic modes is presented that allows for a national individualized strategy designed to achieve maximal biochemical control of GH hypersecretion and elevated IGF-I levels.